Clinical and Preclinical Postgraduate Training in Endodontic Education: A Transnational Exploratory Survey - Venkateshbabu Nagendrababu; Vellore Kannan Gopinath; Mohannad Nassar; Naresh Shetty; Anil Kishen; Paul V. Abbott; Henry F. Duncan (International Dental Journal)
Introduction and aims: Endodontic postgraduate programmes should offer students a wide range of experiences and training in all facets of the specialisation. This study aimed to assess the current postgraduate education practices in endodontics across dental schools worldwide. Methods: The current survey consisted of an online questionnaire that had been validated and piloted. It comprised 68 questions in three sections: general information about the programme, preclinical education, and clinical education. The survey included faculty members who teach postgraduate endodontics from one dental school in each participating country. The data was presented using simple descriptive statistics. Results: In total, 33 faculty members, with a response rate of 85%, from different countries completed the survey. The majority of dental schools that participated in the survey offer a 3-year postgraduate programme. The postgraduate students develop abilities in various instrumentation techniques, irrigation devices, sealers/cements, root canal filling techniques, surgery, and microscope use. Most of the schools conduct a final-year exit examination. Conclusions: Postgraduate education differs globally in its preclinical and clinical training. The survey offers initial insights into postgraduate endodontic education and can help establish mutual educational standards and key focus areas. Clinical relevance: The curricula for preclinical and clinical education in postgraduate endodontics programmes vary globally.